Hypocrisy, State Policy, and African American Students With Disabilities: The Guise of Access. Issue 1 (January 2019) - Tabron, Lolita A.; Ramlackhan, Karen
We critically examined the odds of earning a college preparatory diploma for African American high school seniors receiving special education services under Texas's Top 10% Policy (TTPP). Critical policy analysis was used to explore the meritocratic guise of college access for African American youth with disabilities, and through DisCrit, theorized TTPP's broader effect on the social stratification and creation of policy "winners" and "losers." Results from multilevel logistic regression models indicate African American students are nearly twice as likely to be identified with disabilities as their peers and are the least likely to earn a college preparatory diploma in Texas.